2021
DOI: 10.3389/fvets.2021.769312
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation of Voluntary PRRS Virus Regional Control Programs

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) became pandemic in the 1980's and today remains one of the most significant pathogens of the global swine industry. At the herd level, control of PRRSV is complicated by its extreme genetic diversity and its ability to persist in pigs, despite an active immune response. Ultimately, PRRSV control or elimination requires the coordination and active cooperation of producers and veterinarians at the regional level. Early voluntary PRRSV regional control p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The most frequently used population-based sample types are oral fluids ( 9 ), processing fluids ( 10 ), and family oral fluids ( 11 ). It has been reported that population-based methods increase herd sensitivity without increasing cost, time, and labor ( 10 , 12 ), compared to bleeding a subset of animals.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently used population-based sample types are oral fluids ( 9 ), processing fluids ( 10 ), and family oral fluids ( 11 ). It has been reported that population-based methods increase herd sensitivity without increasing cost, time, and labor ( 10 , 12 ), compared to bleeding a subset of animals.…”
Section: Introductionmentioning
confidence: 99%
“…Annually, up to 19% of Quebec swine breeding herds experience the introduction of at least one new PRRSV strain [18]. To proactively manage the disease, PRRS regional control and elimination (ARC&E) initiatives were established in Quebec [ 21 ], similar to what has been done elsewhere [ 1 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the course of practical implementation of the measures in a farm, effective cooperation has to be established with the pig farm managers and the staff working in each production phase. Eventually, Hungary commenced PRRS eradication of the pig population based on the territorial principle in 2014 [ 10 , 11 ]. The aim of the legislated program was set to eliminate the causative agent of the PRRS disease, including the vaccine virus strains, and reach the PRRS-free status of all pigs.…”
Section: Introductionmentioning
confidence: 99%